2013
DOI: 10.1128/jvi.01474-13
|View full text |Cite
|
Sign up to set email alerts
|

A Host YB-1 Ribonucleoprotein Complex Is Hijacked by Hepatitis C Virus for the Control of NS3-Dependent Particle Production

Abstract: dHepatitis C virus (HCV) orchestrates the different stages of its life cycle in time and space through the sequential participation of HCV proteins and cellular machineries; hence, these represent tractable molecular host targets for HCV elimination by combination therapies. We recently identified multifunctional Y-box-binding protein 1 (YB-1 or YBX1) as an interacting partner of NS3/4A protein and HCV genomic RNA that negatively regulates the equilibrium between viral translation/replication and particle prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 88 publications
8
59
0
Order By: Relevance
“…2F). The results substantiate that YB-1 is essential for the HCV life cycle, as reported by Chatel-Chaix et al (43,44).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…2F). The results substantiate that YB-1 is essential for the HCV life cycle, as reported by Chatel-Chaix et al (43,44).…”
Section: Resultssupporting
confidence: 90%
“…7E) conceivably suggests that YB-1 is important for the production of infectious HCV particles. Interestingly, by using a plasmid-derived JFH-1-expressing system, Chatel-Chaix et al showed that knockdown of YB-1 promoted infectious virus production (43,44). Notably, the kinetics of the plasmid-derived JFH-1 expression is much slower than that of cell culture-derived HCV (HCVcc) infection adopted in our study (22,43).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations